Who invited the undertaker? - Ruckman, Ivy. (New York : T.Y. Crowell, 1989)
Follows the misadventures of seventh-grader Dale as he tries to find a husband for his widowed mother.
Keywords: Mothers -- Fiction; Widows -- Fiction; Family life -- Fiction